Evolution of temperature field of double cone specimen and strut during the heating stage of hot compression. (7th November 2020) - Zou, Yang; Luo, Zizhuo; Wei, Guomeng; Jiang, Liang; Jiang, Bingyan
Abstract: To reasonably select the process parameters of the double cone specimen (DCS) during hot compression, the temperature field evolution in the resistant furnace during the heating stage of hot compression was analyzed by numerical and experimental methods. The results show that there is a significant temperature gradient between surface and center of the specimen during the heating stage, the temperature in the thermal radiant area is higher than the end face. The cooling condition of the strut has no significant effect on the temperature of the specimen, the heat is transferred from the strut to the specimen through the contact surface. Sectional heating can significantly reduce the temperature gradient and the holding time, the temperature difference of specimen is negatively related to the heat treatment time, the equilibration time is negatively related to the holding temperature.